2001
DOI: 10.2323/jgam.47.143
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic position of new bacteriocin (nukacin ISK-1) producer isolated from long-aged Nukadoko.

Abstract: The new lantibiotic nukacin producers, strain ISK-1 previously labeled as Pediococcus sp. ISK-1 and strain Nagano, were characterized biochemically and genetically. Cells were spherical, 0.6 µm in size, and occurred in pairs. The strains were gram-positive, catalase positive and produced more than 75% of DLlactic acid from glucose and their growth was stimulated by mevalonic acid. The strains tolerated 18% NaCl. GϩC content was 36%. 16S rRNA homology revealed that the strains resembled Staphylococcus warneri. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…S. warneri ISK-1 (JCM 11004) isolated from long-aged Nukadoko 3) and Pediococcus pentosaceus JCM 5885 (formerly reported as Pediococcus acidilactici JCM 5885 T ) were grown in MRS medium (Oxoid, Hampshire, U.K.), as described previously. 6) Escherichia coli JM 109 (Toyobo, Osaka, Japan) 17) was grown in LB medium 18) at 37 C. Plasmid pUC18 (Toyobo) was used for cloning of the fragments of the nukacin ISK-1 biosynthetic gene cluster.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…S. warneri ISK-1 (JCM 11004) isolated from long-aged Nukadoko 3) and Pediococcus pentosaceus JCM 5885 (formerly reported as Pediococcus acidilactici JCM 5885 T ) were grown in MRS medium (Oxoid, Hampshire, U.K.), as described previously. 6) Escherichia coli JM 109 (Toyobo, Osaka, Japan) 17) was grown in LB medium 18) at 37 C. Plasmid pUC18 (Toyobo) was used for cloning of the fragments of the nukacin ISK-1 biosynthetic gene cluster.…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5][6] The N-terminal amino acid sequence analysis, amino acid composition analysis, mass spectrum analysis, and structural gene sequence analysis suggested that nukacin ISK-1 consists of 27 amino acids including 2 molecules of lanthionine, 1 molecule of 3-metyllanthionine, and 1 residue of dehydrobutyrine ( Fig. 1).…”
mentioning
confidence: 99%
“…Staphylococcus warneri ISK-1 was isolated from a wellaged Nukadoko , a bed of fermented rice bran [8] . This bacterium produces a novel type-A(II) lantibiotic, nukacin ISK-1 [9] ( fig.…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial strains and plasmids used in this study are listed in Table 1. S. warneri ISK-1 (JCM 11004) 15) was cultured in half concentrated MRS medium (Oxoid, Hampshire, United Kingdom) 18) with shaking at 37 C. L. lactis subsp. lactis CNRZ481 25) was cultured in MRS medium without shaking at 30 C. Escherichia coli JM109 26) used as a cloning host and S. carnosus TM300 27) were grown in LB medium 28) at 37 C. L. lactis NZ9000 29) was grown in M17 medium (Merck, Darmstadt, Germany) supplemented with 0.5% glucose (GM17) at 30 C. Plasmid pNZ8048 30) was used for the expression of nukFEGH.…”
Section: Methodsmentioning
confidence: 99%
“…14) Nukacin ISK-1 is a type-A(II) lantibiotic produced by Staphylococcus warneri ISK-1 (JCM 11004). [15][16][17][18] The putative structure of nukacin ISK-1 (MW 2960 Da) y To whom correspondence should be addressed. Fax: +81-92-642-3019; E-mail: sonomoto@agr.kyushu-u.ac.jp Abbreviation: NICE, nisin-controlled expression agreed with that of lacticin 481 (MW 2901 Da) in terms of number of amino acid residues and position of unusual amino acids.…”
Section: Type-a(i) and Type-a(ii)mentioning
confidence: 99%